Sero Positivity of Hepatitis C among Patients with β-Thalassemia Major in Karbala Center - Muhsin, Akram Hamdi; Hadi, Ammer Muhssin; Naji, Aiub Bassim; Alkhateeb, Dheyaa Aldeen (Academia Open, 2025)
Background: Hepatitis C virus is a major cause of post-transfusion hepatitis infection and remains a significant global health problem. Patients with thalassemia major are at high risk of HCV due to frequent blood transfusions from infected donors. Objective: To evaluate the sero positivity of HCV infection among patients aged 3 to 18 years with β-thalassemia major. Methods: A retrospective study was conducted on 254 patients (131 females, 123 males) attending the Thalassemia Center at Karbala Children's Hospital from August 2014 to March 2015. Ages ranged from 3 to 18 years. Serological viral markers for anti-HCV antibody were tested using enzyme linked immune sorbent assay. Results: Out of 254 patients, 123 (48.4%) were male and 131 (51.6%) were female. Seventeen (6.7%) were seropositive for HCV. Among patients <6 years, 1 (2.3%) was positive; in ages 6-12 years, 7 (5.3%) were positive; and above 12 years, 9 (11.5%) were infected. Blood transfusion frequency showed that 1 (2.2%) of 45 patients receiving <100 transfusions was positive, 6 (5.4%) of 111 receiving 101-200 transfusions, 6 (9.8%) of 61 receiving 201-300 transfusions, and 4 (10.8%) of 37 receiving >300 transfusions were positive. None of the 10 patients who had undergone splenectomy were infected, while 17 (7%) without splenectomy were infected. Among 59,886 volunteer blood donors in Karbala from 2012 to 2014, 54 (0.1%) were anti-HCV positive. Conclusion: Higher rates of HCV infection in older thalassemia patients with more transfusions highlight the importance of accurate blood screening techniques like PCR to prevent infections in thalassemia patients. Highlights: HCV infection increases with patient age and number of transfusions. Older thalassemia patients show higher seropositivity rates. Emphasizes the need for PCR screening to ensure safer transfusions. Keywords: Hepatitis C, Thalassemia Major, Blood Transfusion, Seropositivity, Pediatric Infection